Conceituação, propostas de intervenção e contribuições das terapias cognitivas para o transtorno do espectro autista de alto funcionamento: revisão integrativa da literatura - Teodoro, Marília Consolini (2018)
This study aimed to present two integrative reviews of the literature on Cognitive Therapies and High Performance Autistic Spectrum Disorder (TEA-AF), and after that, present considerations and reflections on the results of both. The first review was published in Portuguese and English in the last ten years on Cognitive Behavioral Therapy and TEA-AF. We searched the BVS, PsychINFO and MedLine databases with the following combinations: "Cognitive Behavior Therapy" and "Autism Spectrum Disroder"; "Behavioral Cognitive Therapy" and "Autistic Spectrum Disorder". 40 articles were selected. The results showed that most of the articles are of the Randomized Controlled Clinical Trial type, with group interventions, parental involvement and anxiety focus. In addition, traditional CBT techniques were maintained in most of them, but with adaptations in them and in protocols. The adaptations that appeared the most were the use of visual stimuli and personal interests of the patient. The most used instruments for diagnostic closure were ADOS and WISC-IV. There was a great divergence in the instruments used in evaluating interventions. The results suggest that CBT is feasible for TEA-AF, but with adaptations. In addition, they suggest the creation of instruments that assess the manifestation of anxiety and other comorbidities in this population. The second review was published in the Portuguese, English and German language of the last ten years on Scheme Therapy and TEA-AF. We searched the VHL, PsychINFO, MedLine, ZDB and WZB databases with the following combinations: "Schema Therapy" and "Autism Spectrum Disorder"; "Schema Therapy" and "Autism Spectrum Disorder"; and "Schematherapie" and "Autismus-Spektrum-Störungen". Three papers were selected, two articles and one book chapter. The results showed that possible EIDs related to ASD-AF are: Emotional Deprivation, Social Isolation; Inflexible Standards, Vulnerability to Damage and Disease, Insufficient self-control and self-discipline, and Grandiosity. In working with children, there is a need for parental involvement. The suggested interventions are mainly psychoeducation, experiential techniques and work with Modes, with adaptations. The results show that the TE presents a theoretical model on the TEA-AF, with contributions that can go beyond the intervention for the presented symptoms. In common between the two approaches, there is the importance of parental involvement and adaptations of techniques. As divergences, CBT shows a very advanced therapy in the care of this population, with effective empirical studies, however, without any theoretical work that relates the disorder to theoretical models of CBT. The Scheme Therapy, on the other hand, has few and unpublished works in the subject, however, it presents contributions that relate the disorder to the Theory, which can contribute to the advance of the researches in the area. It is concluded that people with ASF-AF can benefit from CBT care, and Scheme Therapy is a possible alternative for the care of this population. Keywords: Autism Spectrum Disorder; Cognitive behavioral therapy; Schema Therapy.